2010 IEEE International Conference on Industrial Technology 2010
DOI: 10.1109/icit.2010.5472544
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sizing of a hybrid renewable system

Abstract: Sizing of an electric power generation system requires an analysis of the investment, maintenance, and operation costs. In the case of a generation system that uses renewable sources the sizing it is more complex with regard to a conventional system, due to the randomness of the renewable resources, and to the even high costs of wind generators and photovoltaic modules. This paper presents the optimal sizing of a generation system wind-photovoltaic-fuel cell such that demand of an isolated residential load is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The main goal of sizing the hybrid wind/PV system is to minimize the total cost, this includes capital cost and Operations & Maintenance cost [9]. HOMER investigates feasibility of the proposed hybrid system.…”
Section: System Components Costsmentioning
confidence: 99%
“…The main goal of sizing the hybrid wind/PV system is to minimize the total cost, this includes capital cost and Operations & Maintenance cost [9]. HOMER investigates feasibility of the proposed hybrid system.…”
Section: System Components Costsmentioning
confidence: 99%
“…There are different types of optimization methods that are recommended by various studies to determine the size of the stand-alone hybrid systems optimally. Among the various optimization methods, the genetic algorithm [26,27], particle swarm optimization [28], tabu search [29], and mixed integer nonlinear programming [30] are the most used for hybrid systems optimization. In hybrid system size optimization, the minimum system cost is the most common and important objective; some other objectives like environmental and technical requirements are also incorporated in the optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, similar to GA, PSO may have issues when encountering a problem with many parameters, such as ELD with RE integration [9]. Nonetheless, in [10], [11], PSO was still used to optimize the sizing of PV-wind turbine hybrid system. The studies revealed that PSO successfully optimizes the complex ELD problem albeit the major drawback.…”
Section: Introductionmentioning
confidence: 99%